STRATEGIES CONSIDERED EFFECTIVE FOR TEACHING ENTREPRENEURSHIPBY BUSINESS SUBJECT TEACHERS IN SECONDARY SCHOOLS IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study sought to ascertain the opinions of business subject teachers on thestrategies considered effective for teaching entrepreneurship in secondary schools inAnambra State. Two research questions and four hypotheses guided the study.Descriptive survey research design was adopted for the study. The populationcomprised 513 business subject teachers. A sample size of 244 business subjectteachers was selected for the study using simple random sampling technique. Astructured and validated questionnaire with 18 items was used for data collection.Mean was used to answer the research questions while standard deviation was usedto check how close or otherwise of the respondents responses to the mean. t-test andANOVA were used to test the hypotheses. Findings of the study revealed that the useof information and communication technology and school-industry partnership werehighly effective strategies for teaching entrepreneurship. Based on the findings of thestudy, it was concluded that information and communication technology strategiesand school industrial collaboration strategies are considered highly effective forteaching entrepreneurship. It was also concluded that gender and type of school donot affect the strategies considered effective for teaching entrepreneurship. It wasrecommended amongst others that, the Anambra State Government should providefunds for secondary school management, regular training and retraining programmesof business subject teachers both in public secondary schools to enable them updatetheir ICT skills so as to utilize new technologies for instructional purposes.